(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Based on the analysis of the existing definitions of the concepts of "coordination abilities", the article reveals their types in rhythmic gymnastics, which are classified as special motor abilities and specialized perceptions or"feelings".